2015
DOI: 10.1002/dneu.22279
|View full text |Cite
|
Sign up to set email alerts
|

Development of the stria vascularis and potassium regulation in the human fetal cochlea: Insights into hereditary sensorineural hearing loss

Abstract: Sensorineural hearing loss (SNHL) is one of the most common congenital disorders in humans, afflicting one in every thousand newborns. The majority is of heritable origin and can be divided in syndromic and nonsyndromic forms. Knowledge of the expression profile of affected genes in the human fetal cochlea is limited, and as many of the gene mutations causing SNHL likely affect the stria vascularis or cochlear potassium homeostasis (both essential to hearing), a better insight into the embryological developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 82 publications
6
68
1
1
Order By: Relevance
“…The expression of Cx43 in the mature organ of Corti appears negligible, however Cx43 is temporally expressed during development of the human and mouse inner ear (Cohen-Salmon et al, 2004;Locher et al, 2015). Hearing loss-linked Cx26 mutants may therefore be co-expressed with Cx43 during the development of the inner ear.…”
Section: The S183f Mutant Intermixes With Endogenous Cx43 Gap Junctionsmentioning
confidence: 99%
“…The expression of Cx43 in the mature organ of Corti appears negligible, however Cx43 is temporally expressed during development of the human and mouse inner ear (Cohen-Salmon et al, 2004;Locher et al, 2015). Hearing loss-linked Cx26 mutants may therefore be co-expressed with Cx43 during the development of the inner ear.…”
Section: The S183f Mutant Intermixes With Endogenous Cx43 Gap Junctionsmentioning
confidence: 99%
“…CX26 and CX30 form heteromeric and heterotypic channels in most of the cochlear gap junction plaques (GJPs) (Sun et al., 2005) and in in vitro experiments (Yum et al., 2007). Recently, expression of various transcription factors and other proteins in human developmental fetal cochleae from gestational weeks 9–22 were investigated using immunohistochemistry (Locher et al., 2013, Locher et al., 2014), and it has been found that the expression of CX26 and CX30 is detectable in the outer sulcus cells at 18 weeks of gestation (Locher et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Mutations in genes that disrupt the flow of potassium ions through the multilayered stria vascularis, including gap junctions, channels, pumps and transporters, are common causes of hearing loss (Locher et al, 2015). Despite their importance for auditory function, relatively little is known about the development of lateral cochlear duct cells, compared to their sensory counterparts.…”
Section: Introductionmentioning
confidence: 99%